Restructuring and privatization of public enterprises in Canada: Legal and financial aspects - Grahovac Borislav (Međunarodni Problemi, 2007)
The theme of the paper is restructuring and privatization of public enterprises in Canada, where the enterprise operates as a business offering public goods or services. Legal and financial aspects of public enterprises distinguish those enterprises from other businesses and government activities. The author analyzes and compares various experiences with different forms of public enterprises. The study explains goals, essence, definition and differences between similar enterprises and other government activities and private enterprises. The paper provides a stimulating debate about the ways to reform public enterprises in different countries.